THE SEMANTICS OF EMOTION WORDS ACROSS CULTURES: A CROSS-LINGUISTIC PERSPECTIVE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Emotions are universal, yet their linguistic representation differs across cultures. This paper explores how emotion words are categorized in different languages, highlighting both universal structures and cultural variations. Through an analysis of existing literature, this study examines how emotions are perceived, categorized, and influenced by linguistic relativity. The research finds that while emotions are broadly classified along dimensions of valence, arousal, and dominance, cultural norms shape their interpretation and expression. These findings have implications for cross-cultural communication, psychology, and artificial intelligence.